Downscaling With an Unstructured Coastal-Ocean Model to the Goro Lagoon and the Po River Delta Branches - Maicu, Francesco; Alessandri, Jacopo; Pinardi, Nadia; Verri, Giorgia; Umgiesser, Georg; Lovo, Stefano; Turolla, Saverio; Paccagnella, Tiziana; Valentini, Andrea (Frontiers in Marine Science, 2021)
The Goro Lagoon Finite Element Model (GOLFEM) presented in this paper concentrates on the high-resolution downscaled model of the Goro Lagoon, along with five Po river branches and the coastal area of the Po delta in the northern Adriatic Sea (Italy) where crucial socio-economic activities take place. GOLFEM was validated by means of validation scores (bias – BIAS, root mean square error – RMSE, and mean absolute error – MAE) for the water level, current velocity, salinity and temperature measured at several fixed stations in the lagoon. The range of scores at the stations are: for temperature between −0.8 to +1.2°C, for salinity from −0.2 to 5 PSU, for sea level 0.1 m. The lagoon is dominated by an estuarine vertical circulation due to a double opening at the lagoon mouth and sustained by multiple sources of freshwater inputs. The non-linear interactions among the tidal forcing, the wind and the freshwater inputs affect the lagoon circulation at both seasonal and daily time scales. The sensitivity of the circulation to the forcings was analyzed with several sensitivity experiments done with the exclusion of the tidal forcing and different configurations of the river connections. GOLFEM was designed to resolve the lagoon dynamics at high resolution in order to evaluate the potential effects on the clam farming of two proposed scenarios of human intervention on the morphology of the connection with the sea. We calculated the changes of the lagoon current speed and salinity, and using opportune fitness indexes related to the clams physiology, we quantified analytically the effects of the interventions in terms of extension and persistence of areas of the clams optimal growth. The results demonstrate that the correct management of this kind of fragile environment relies on both long-term (intervention scenarios) and short-term (coastal flooding forecasts and potential anoxic conditions) modeling, based on a flexible tool that is able to consider all the recorded human interventions on the river connections. This study also demonstrates the importance of designing a seamless chain of models that are capable of integrating local effects into the coarser operational oceanographic models.